2021
DOI: 10.1051/e3sconf/202131901067
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial power of Olea Europaea extracts from different Moroccan regions

Abstract: The discovery of antibiotics has always been a medical advance that has improved the prognosis of infections. However, resistance to these products has evolved into a major health problem. Some diseases are even resistant to all antibiotics currently available on the market. A reduction in the use of antibiotics must be based on other approaches, namely the use of alternative treatments to antibiotics, such as phytotherapy. In the same objective our study focused on the research of the antibacterial power of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(5 reference statements)
0
0
1
Order By: Relevance
“…All bacteria resisted the hexane and chloroform extracts of O. europaea (Figure 4a-e). O. europaea demonstrated resistance against Staphylococcus, contrary to the study by Ben-Amor et al [26], which showed anti-staphylococcal activity of O. europaea leaf extract. Our results were similar to the study by Sahraoui et al [27].…”
Section: Discussioncontrasting
confidence: 86%
“…All bacteria resisted the hexane and chloroform extracts of O. europaea (Figure 4a-e). O. europaea demonstrated resistance against Staphylococcus, contrary to the study by Ben-Amor et al [26], which showed anti-staphylococcal activity of O. europaea leaf extract. Our results were similar to the study by Sahraoui et al [27].…”
Section: Discussioncontrasting
confidence: 86%